STRES KERJA, KOMITMEN ORGANISASIONAL DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN - Edi Siregar (Jurnal Manajemen, 2017)
This research aims to know the influence of job stress, organizational commitment and organization climate has an effect to job satisfaction of employee in the office PT. Agrindo Prima Lestari. The sampling technique of this research is using census sampling, where the sampling is the all population of employees in PT. Agrindo Prima Lestari. Statistical analysis method in this research used the multiple linear regressions with the help of SPSS 22 software. Based on the result of the analysis conclude that 1) job stress has no effect to job satisfaction, 2) organizational commitment has significant effect to job satisfaction, 3) organization climate has significant effect on job satisfaction 4) job stress, organizational commitment and organization climate is jointly significant effect on employee job satisfaction.